Digital Literacy Composing Poems Using Quote Creator for Students' Writing Skill - Hasan Basri, linta Wafdan Hidayah, fitrah Yuliawati (Journal of Educational Studies, 2025)
This study aims to describe the implementation of the Quote Creator application in poetry writing activities and to describe the results of composing poems using the application for second-semester students. A descriptive qualitative approach was employed, involving 28 second-semester students from the English Education Department at Universitas Islam Madura, Indonesia. Data were collected through observation, semi-structured interviews, and documentation. The findings reveal that the implementation of Quote Creator went through three stages: feature exploration, guided writing, and publication. Students developed multimodal awareness by combining text and visual elements such as colors, backgrounds, images, and fonts to strengthen the meaning of their poems. Students wrote about personal themes including family affection, simplicity, nature, hope, and love, using simple yet communicative English. Increased student confidence was reported because the digital format produced neat and visually appealing results. However, challenges in arranging words in English indicated the need for continued pedagogical guidance. This study suggests that Quote Creator, when used with appropriate teacher guidance, can serve as an effective offline digital tool for creative writing instruction.